THE REASONABLE USE OF LIGNITE IN INDUSTRY AND RELEVANCE OF OBTAINING BRIQUETTES (Innovative Technologica: Methodical Research Journal, 2023)
In the article, the internal composition of coal extracted from mines, its use, combustion properties and the amount of ash produced as a result of combustion are studied. Based on the obtained results, the solutions were analyzed.